Correlates of neural adaptation to food cues and taste: the role of obesity risk factors. Issue 1 (3rd March 2021) - Sadler, Jennifer R; Shearrer, Grace E; Papantoni, Afroditi; Yokum, Sonja T; Stice, Eric; Burger, Kyle S
Abstract: Identifying correlates of brain response to food cues and taste provides critical information on individual differences that may influence variability in eating behavior. However, a few studies examine how brain response changes over repeated exposures and the individual factors that are associated with these changes. Using functional magnetic resonance imaging, we examined how brain response to a palatable taste and proceeding cues changed over repeated exposures and how individual differences in weight, familial obesity risk, dietary restraint and reward responsiveness correlate with these changes. In healthy-weight adolescents ( n  = 154), caudate and posterior cingulate cortex (PCC) response increased with repeated cue presentations, and oral somatosensory cortex and insula response increased with repeated milkshake tastes. The magnitude of increase over exposures in the left PCC to cues was positively associated with body mass index percentile ( r  = 0.18, P  = 0.026) and negatively associated with dietary restraint scores ( r  = −0.24, P  = 0.003). Adolescents with familial obesity risk showed higher cue-evoked caudate response across time, compared to the low-risk group ( r  = 0.12, P  = 0.035). Reward responsiveness positively correlated with right oral somatosensory cortex/insula response to milkshake over time ( r  = 0.19, P  = 0.018). The results show that neural responses to food cues and taste change over time and that individual differences related to weight gain are correlated with these changes.